Crisis Communication in the Eviction of Street Vendors in the Puncak Bogor Area : Application of the Nine Elements of Journalism in Kumparan.com Coverage - Aditya Kurniawan (Journal of Content and Engagement, 2025)
Urban street vendor evictions frequently generate social tension in developing countries, particularly where informal economies intersect with state-led spatial governance. This study examines crisis communication practices in digital journalism through an analysis of Kumparan.com’s coverage of street vendor evictions in the Puncak area of Bogor, Indonesia. Using a qualitative content analysis approach, the research investigates how media framing, agenda-setting mechanisms, and the nine elements of journalism are applied in reporting policy-driven social conflict. Data were collected from ten news articles published between June and July 2024, supplemented by audience comment observation and in-depth interviews with Kumparan.com readers. The findings reveal that while Kumparan.com presents multiple perspectives and demonstrates adherence to journalistic principles such as verification and watchdog functions, inconsistencies persist in maintaining editorial independence and balanced representation of marginalized street vendors. Government narratives tend to receive greater prominence, potentially shaping public acceptance of eviction policies. This study highlights the influential role of digital media in shaping public discourse during crisis situations and underscores the need for ethical, inclusive, and conflict-sensitive journalism. The findings offer practical implications for journalists and policymakers seeking to improve crisis communication strategies and democratic accountability in digital news environments.